Immunohistochemical staining of Langerhans cells in HPV-positive and HPV-negative cases of oral squamous cells carcinoma - Karuza Maria Alves Pereira; Rosilene Calazans Soares; Márcio Campos Oliveira; Leão Pereira Pinto; Antônio de Lisboa Lopes Costa (University of São Paulo, 2011)
The Human Papillomavirus (HPV) has been strongly implicated in development of some cases of oral squamous cell carcinoma (OSCC). However, the immunological system somehow reacts against the presence of this virus. Among the cells involved in such mechanism of defense Langerhans cells (LC) stand out, which are responsible for processing and presenting antigens. OBJECTIVES: The purposes of this study were to investigate the presence of HPV DNA and to evaluate the immunohistochemical reactivity for Langerhans cells between HPV-positive and HPV-negative OSCC. Twenty-seven cases of OSSC were evaluated. MATERIAL AND METHODS: DNA was extracted from paraffin-embedded tissue samples and amplified by Polymerase Chain Reaction (PCR) for the detection of HPV DNA. Viral typing was performed by dot blot hybridization. Immunohistochemistry was performed by the Streptavidin-biotin technique. RESULTS: From the 27 cases, 9 (33.3%) were HPV-positive and 18 (66.0%) HPV-negative. HPV 18 was the most prevalent viral type (100% cases) and infection with HPV-16 (co-infection) was detected in only 1 case. In the OSCC specimens examined, immunoreactivity to S-100 antibody was detected in all cases, with a mean number of 49.48±30.89 Langerhans cells positive for immunostaining. The mean number of immunostained Langerhans cells was smaller in the HPV-positive cases (38 cells/case) than in the HPV-negative cases (42.5 cells/case), but this difference was not significant (p=0.38). CONCLUSIONS: The low frequency of detection of HPV DNA in OSCC indicates a possible participation of the virus in the development and progression of only a subgroup of these tumors. There was no association between the immunohistochemical labeling for Langerhans cells (S-100+) and HPV infection of in OSSC. These findings suggest that the presence of HPV in such OSCC cases could not alter the immunological system, particularly the Langerhans cells.